2020
DOI: 10.1177/1356766720943624
|View full text |Cite
|
Sign up to set email alerts
|

The influence of theocratic rule and political turmoil on tourists’ length of stay

Abstract: The average tourist’s length of stay (LOS) is in a global decline. This downward trend underscores the need to study the factors that affect this variable in order to enable more effective management and marketing. This paper moves beyond the literature by investigating the determinants of international tourists’ LOS in a Muslim destination amid political crisis. LOS was evaluated using a survival analysis approach with data from 726 international tourists in Tabriz, Iran to ascertain the significant factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 61 publications
(201 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have attempted to ascertain the determinants of the LoS of tourists to provide useful insight into how to increase the LoS effectively. Practitioners need to understand the determinants of LoS to develop effective target marketing strategies (Hateftabar and Chapuis, 2020; Hateftabar, 2021). For example, Wang et al (2018) revealed the determinants of LoS in the context of a gaming destination, Macao.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have attempted to ascertain the determinants of the LoS of tourists to provide useful insight into how to increase the LoS effectively. Practitioners need to understand the determinants of LoS to develop effective target marketing strategies (Hateftabar and Chapuis, 2020; Hateftabar, 2021). For example, Wang et al (2018) revealed the determinants of LoS in the context of a gaming destination, Macao.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Numerous studies have examined how the LoS directly contributes to profitability (Weatherford, 1995). In addition, previous studies have attempted to reveal the determinants of LoS to provide useful insights for practitioners to formulate effective target marketing strategies (Hateftabar and Chapuis, 2020; Hateftabar, 2021). As a result, various socioeconomic factors were found to be closely related to the LoS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LOS studies differ in terms of geographical location, influencing variables, and methodologies (Hateftabar & Chapuis, 2020). Previous studies have covered several geographical locations, as discussed in the introduction section; they include Spain, the southern coast of Portugal, the Atlantic coast of the United States, Norway, and the mountains of Italy.…”
Section: Tourists' Length Of Staymentioning
confidence: 99%
“…Previous studies have covered several geographical locations, as discussed in the introduction section; they include Spain, the southern coast of Portugal, the Atlantic coast of the United States, Norway, and the mountains of Italy. In addition, various methodological approaches, such as survival analysis (Aguilar & Díaz, 2019;Hateftabar & Chapuis, 2020), count regression (Nicolau et al, 2018), OLS regression (Thrane, 2015), and logit regression (Alegre & Pou, 2006) have been adopted to model LOS.…”
Section: Tourists' Length Of Staymentioning
confidence: 99%
See 1 more Smart Citation